Introduction: Academic Labour, Digital Media and Capitalism - Thomas Allmer; Ergin Bulut (tripleC: Communication, Capitalism & Critique)
The overall task of this special issue of tripleC: Communication, Capitalism & Critique is to gather critical contributions examining universities, academic labour, digital media and capitalism. The articles collected in this special issue (1) provide the context, history and theoretical concepts underlying academic labour, (2) analyse the relationship between academic work and digital media/new information and communication technologies/the Internet/social media, and (3) discuss the political potentials and challenges within and beyond higher education institutions.